Urgensi Pendidikan Kewarganegaraan Berbasis Multikultural dalam Pembinaan Keberagaman Masyarakat Indonesia - Julita Widya Dwintari (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
Indonesia is a country that has a lot of diversity in society. Diversity is often seen as adifference, the difference being sharpened and often used by some to fulfill theambitions and interests of the individual or group. This led to horizontal conflicts thatled to the decline of the Indonesian nation, and the occurrence of riots everywhere.The purpose of this article is to describe the urgency of Civic Education based onmulticultural in fostering the diversity of Indonesian society. This research method isliterature review. Multicultural based Citizenship Education (PKn) plays a veryimportant role in fostering the diversity of Indonesian society so that diversity is not asource of conflict, but rather as a basis in tolerating and respecting the diversity thatexists in order to realize the state of Indonesia with Unity in Diversity. Civic learningbased on multicultural education is a simple method and strategy, in order to createthe character of the nation's children who can live in the nuances of difference.Therefore, in the learning process students should be brought closer to thecommunity, life and mutuality in society. Students should be familiar and trained indealing with and solving existing diversity problems in society. Civics teachers mustmake a self-transformation and self-restoration to prepare themselves for guardingand teaching on a multicultural basis. Teachers should get guidance and direction inorder to play a maximum role so that multicultural education can be implementedthrough Civics well. Multicultural education in both Civics and other subjects shouldbe improved especially in former conflict areas and areas with considerable potentialto prevent a recurrence of the conflict.